Ecology and reproductive biology of two species of Aplastodiscus (Anura : Hylidae) in the Atlantic forest, Brazil - Zina, Juliana; Haddad, Celio F. B. (Taylor & Francis Ltd, 2006)
The present study was conducted in the Serra do Japi in the State of São Paulo, Brazil. From March 2004 to January 2006 we studied the ecology and reproductive biology of two sympatric species of Aplastodiscus in three different habitats: lake, stream, and swamp. The majority of A. leucopygius males in calling activity were recorded during the rainy season and during sporadic rains in the dry season (April to September). The same was observed for A. arildae. Most courtship displays of A. leucopygius were observed mainly during the rainy period and only one courtship behaviour was observed for A. arildae during a rainy night, in December 2005. Aplastodiscus leucopygius males were found in activity in the three habitats surveyed. In contrast, males of A. arildae were found in only one habitat (stream). Spatial distribution seems to be the main mechanism of reproductive segregation between the studied species.
Keywords: Anura; Aplastodiscus; ecology; reproductive biology; spatial segregation